Islamic Green Finance dalam Perspektif Pembangunan Daerah: Analisis Potensi Sektor Unggulan, Kesesuaian Maqāṣid al-Syarī‘ah, dan Kesiapan Ekosistem Lokal di Kota Makassar: Islamic Green Finance in the Perspective of Regional Development: An Analysis of Leading Sector Potentials, Alignment with Maqāṣid al-Sharī‘ah, and the Readiness of the Local Ecosystem in Makassar City - Azwar Azwar; Khaerul Aqbar (AL-QIBLAH: Jurnal Studi Islam dan Bahasa Arab, 2026)
The growing urgency of sustainable development and the need to integrate economic, environmental, and Sharī‘ah values drive the development of Islamic Green Finance (IGF) at the regional level; however, integrative studies on leading sectors, maqāṣid al-sharī‘ah, and ecosystem readiness remain limited, particularly in the context of Makassar City. The study pursues three objectives: (1) identifying leading sectors suitable for IGF based on economic value, environmental sustainability, and compatibility with Islamic financial instruments; (2) assessing their alignment with maqāṣid al-sharī‘ah; and (3) evaluating the readiness of the local ecosystem while formulating an integrative, locally grounded strategic framework. A qualitative descriptive-exploratory approach was employed. The maqāṣid al-sharī‘ah assessment applied a normative framework, while ecosystem readiness was examined through thematic analysis of regulatory, institutional, capacity, and societal dimensions. The findings indicate that IGF holds strong potential as a sustainable development instrument in Makassar. Key sectors include renewable energy and waste management, sustainable agriculture and fisheries, halal tourism, and ecosystem rehabilitation. These sectors align with green economy principles and demonstrate compatibility with Islamic finance. Normatively, IGF supports the objectives of maqāṣid al-sharī‘ah, particularly in preserving life, wealth, the environment, and future generations. The local ecosystem shows a positive trajectory, supported by government commitment, emerging industry practices, institutional capacity, and growing public awareness. However, challenges remain in regulatory support, product innovation, institutional capacity, and financial literacy. The study proposes a four-pillar framework: regulatory strengthening, innovative financial instruments, capacity enhancement, and community engagement, implemented through multi-stakeholder collaboration to advance inclusive and sustainable regional development.